Direct Comparison of Leaf Plasmodesma Structure and Function in Relation to Phloem-Loading Type. Issue 4 (5th February 2019) - Liesche, Johannes; Gao, Chen; Binczycki, Piotr; Andersen, Signe R.; Rademaker, Hanna; Schulz, Alexander; Martens, Helle Juel
Abstract : Live - cell and electron microscopy reveal differences between species in how the structure of cell connections relates to the inter-cellular transport capacity for small molecules. Abstract: The export of photosynthetically produced sugars from leaves depends on plasmodesmatal transport of sugar molecules from mesophyll to phloem. Traditionally, the density of plasmodesmata (PD) along this phloem-loading pathway has been used as a defining feature of different phloem-loading types, with species proposed to have either many or few PD between the phloem and surrounding cells of the leaf. However, quantitative determination of PD density has rarely been performed. Moreover, the structure of PD has not been considered, even though it could impact permeability, and functional data are only available for very few species. Here, a comparison of PD density, structure, and function using data from transmission electron microscopy and live-cell microscopy was conducted for all relevant cell–cell interfaces in leaves of nine species. These species represent the three principal phloem-loading types currently discussed in literature. Results show that relative PD density among the different cell-cell interfaces in one species, but not absolute PD density, is indicative of phloem-loading type. PD density data of single interfaces, even combined with PD diameter and length data, did not correlate with the intercellular diffusion capacity measured by the fluorescence loss in photobleaching method. This means that PD substructure not visible on standard transmission electron micrographs may have a strong influence on permeability. Furthermore, the results support a proposed passive symplasmic loading mechanism in the tree species horse chestnut ( Aesculus hippocastanum ), white birch ( Betula pubescens ), orchard apple ( Malus domestica ), and gray poplar ( Populus x canescens ) as functional cell coupling and PD structure differed from active symplasmic and apoplasmic phloem-loading species.